Visualization for UiTM timetable generation system using timetable JavaScript Plugin / Muhammad Faisal Norsham - Norsham, Muhammad Faisal (2020)
This dissertation is motivated to develop an application that helps students manage and visualize their class schedule. By beginning a brief discussion related to timetable and class schedule, this study will expand the foundation for developing a functional and acceptable system that is capable of generating timetable based on a specific student’s class schedule. The first objective would be to design and develop a web application called Timetable Generation System. The second objective is to evaluate the functionality and user acceptance towards the said system. The system’s significance could ease the process of finding and arrange the student’s class schedule in a timetable which will dramatically reduce the time it takes for students to prepare their class schedule timetable every semester. Literature review will be discussed in various topics from class schedule timetabling to web application development. Three related works are included to analyse the related problems of the previous work done by other researchers and study the methods and approaches they used in developing their system. The methodology will discuss the SDLC approach in developing the project. The project development consists of four phases; analysis, design, development and testing. The system was evaluated using functional testing and User Acceptance Test. The tests were conducted in order to verify the system meet user requirements and users accept the developed system respectively. The author may improve the Timetable Generation System in the future by implementing a fully automatic application that require less input from users as well as developing a mobile platform version of the application. There is also a potential study to design and develop the same application but for examination schedule instead.